Cooperative Learning Process in the 21st Century Era: Does It Still Have an Impact on Students' Understanding of Concepts? - Syefrinando, Boby; sofna, Ayu; Pramita, Cici; Puri, Tasa; Adha, Al Fajri; Yuliasih, Yuliasih; Sulman, Fauzan (Edumaspul: Jurnal Pendidikan, 2023)
This research was conducted to determine the effect of the Cooperative Learning learning model on understanding concepts in business and energy material. This type of research is quantitative research. The population in this study were all students of class The sampling technique was carried out using a purposive sampling technique because the data previously obtained from the three classes was normal and homogeneous. The design in this research is post-test only because the samples used have initial abilities that can be said to be the same. Based on data analysis, the average score for the experimental class was 52.3 and the average score for the control class was 47.6. Apart from obtaining the average value, in this study it was also found from the results of the t test that Cooperative Learning learning did not have a significant influence on classes that did not use the Cooperative Learning learning model.